Antibodies associated with paraneoplastic neurological disorders. - Vincent, A (2005)
Certain cancers, particularly small cell lung cancer, gynaecological or breast and also testicular, prostate, bowel and other cancers, can be associated with diverse and often heterogeneous neurological syndromes. In those cases with neurological syndromes, a proportion of patients will have a serum antibody to a defined antigen that is expressed both by the tumour and by the nervous system. The presence of the neurological syndrome often precedes the recognition of the tumour, and thus the detection of one of the specific antibodies leads to a search for the relevant tumour. In general, the antibodies are detected by immunohistochemistry or immunofluorescence on brain tissue. Their specificity can then be confirmed either by western blotting of neuronal or brain extracts, or by western blotting of the specific recombinant protein. There are also some ELISA assays available for detection of antibodies to specific antigens.